Analysis of Pathogenicity and Virulence Factors of Ageratum leaf curl Sichuan virus - Li, Pengbai; Jing, Chenchen; Ren, Hongyan; Jia, Zhou; Ghanem, Hussein; Wu, Gentu; Li, Mingjun; Qing, Ling (Frontiers in Plant Science, 2020)
Ageratum leaf curl Sichuan virus (ALCScV) is a novel monopartite begomovirus, which was identified from Ageratum conyzoides plants in Sichuan Province, China. In this study, we showed that ALCScV can successfully undergo systemic infection and induce typical dwarf and downward leaf-curling symptoms in Ageratum conyzoides, Helianthus annuus and Nicotiana benthamiana plants, and that the noncognate betasatellite can enhance disease symptoms and increase viral accumulation. Expression of the ALCScV-encoded V2, C1, and C4 proteins through a Potato virus X (PVX) vector caused severe symptoms in N. benthamiana. Further study revealed no symptoms in N. benthamiana plants inoculated with infectious ALCScV clones lacking the C4 protein and that the relative viral DNA accumulation levels significantly decreased when compared with ALCScV-inoculated plants. Thus, our mutational analyses demonstrated that C4 is a pathogenicity determinant that plays key roles in symptom formation and virus accumulation. Furthermore, we also demonstrated that the second glycine of C4 was critical for ALCScV pathogenicity.